The validity of the practical examination from the perspective of experts in initial vocational education in the retail trade sector in Switzerland - Jan, David (Mesure et évaluation en éducation)

(untitled) (ADMEE-Canada, 2024)
In Switzerland, at the end of their initial vocational education, retail apprentices take a practical exam at the company where they are being trained. This exam, which is both certifying and eliminating, lasts between one and one and a half hours, depending on the type of training. It is conducted by two professionals in the field known as examiners. The objectives of this study are, firstly, to understand the validity attributed to the practical exam by the examiners and, secondly, to define the reasons for this assessment. To achieve this, a sample of 189 examiners answered a questionnaire on the validity of this exam. The data were processed by exploratory factor analysis, and three expert profiles were extracted by latent classes. The results of this study highlighted the heterogeneity of the examiners profiles. They differ according to their experience as examiners and their language.